Evaluating institutional fit for the conservation of threatened species. Issue 5 (5th May 2021) - Guerrero, A. M.; Sporne, I.; McKenna, R.; Wilson, K. A.
Abstract: Recovery and conservation of threatened species require adequate institutional responses. We tested an approach to systematically identify and measure how an institutional framework acknowledges threats and required responses for the recovery of endangered species. We measured institutional functional fit with a drivers‐pressure‐state‐impacts‐response (DPSIR) model integrated with a quantitative text mining method and qualitative analysis of statutory instruments to examine regulatory responses that support the recovery of 2 endangered species native to Australia, the bridled nailtail wallaby ( Onychogalea fraenata ) and the Eastern Bristlebird ( Dasyornis brachypterus ). The key components of the DPSIR model were present in the institutional framework at statutory and operational levels, but some institutional gaps remained in the protection and recovery of the Eastern Bristlebird, including feral predator control, weed control, and grazing management in some locations. However, regulatory frameworks varied in their geographic scope and the application and implementation of many instruments remained optional. Quantitative text mining can be used to quickly navigate a large volume of regulatory documents, but challenges remain in selection of terms, queries of co‐occurrence, and interpretation of word frequency counts. To inform policy, we recommend that quantitative assessments of institutional fit be complemented with qualitative analysis and interpreted in light of the sociopolitical and institutional context. Abstract : Article impact statement : Mixed‐methods approaches to functional‐fit analyses can help identify institutional barriers to the management of threatened species. Resumen: La recuperación y la conservación de las especies amenazadas requieren de respuestas institucionales adecuadas. Evaluamos una estrategia para identificar y medir sistemáticamente cómo un marco de trabajo reconoce las amenazas y las respuestas requeridas para la recuperación de las especies en peligro. Medimos la aptitud funcional institucional mediante un modelo de fuerzas motrices‐presión‐estado‐impacto‐respuesta (DPSIR) integrado con un método cuantitativo de extracción de textos y un análisis cualitativo de los instrumentos legales para examinar las respuestas regulatorias que apoyan a la recuperación de dos especies en peligro nativas de Australia: Onychogalea fraenata y Dasyornis brachypterus . Los componentes clave del modelo DPSIR estuvieron presentes en el marco de trabajo institucional a niveles legales y operativos, pero algunos vacíos institucionales permanecieron en la protección y recuperación de D. brachypterus, incluyendo el control de depredadores ferales, el control de malezas y el manejo del pastoreo en algunas localidades. Sin embargo, los marcos de trabajo regulatorios variaron en cuanto a su enfoque geográfico y la aplicación e implementación de muchos de los instrumentos siguieron siendo opcionales. La extracción cuantitativa de textos puede usarse para navegar rápidamente un gran volumen de documentación regulatoria, pero todavía existen obstáculos en la selección de términos, consultas sobre la coocurrencia e interpretación de los conteos de frecuencia de palabras. Para orientar a las políticas recomendamos que las evaluaciones cuantitativas de la aptitud institucional estén complementadas con análisis cuantitativos e interpretadas a la luz del contexto institucional y sociopolítico.